An exploratory study to investigate the relationship between social license to operate and sustainable development strategies. (26th May 2019) - Panda, Swapna Sonali; Sangle, Shirish
Abstract: A social license to operate (SLO) has become imperative for extractive and resource‐intensive industries due to their high potential for conflicts. Firms are still struggling to maintain their SLO despite its growing importance. Because most of the extractive industries orient on sustainable development strategies (SDS), this paper investigates the relationship between SLO and SDS through an exploratory study by means of eight semistructured in‐depth interviews. Content analysis of these interviews is done by Atlas.ti software. In essence, this paper provides a perspective on how firms working in extractive industries can employ SDS to gain and maintain an SLO. Along with focus SLO, the study reveals the growing importance of stakeholders in the said industries and gives the direction of how managing the stakeholders can help the firms in the long run.